Knowledge of breast cancer and practice of breast self-examination among adolescent girls in semi-urban area – Savar, Dhaka, Bangladesh: A school-based cross-sectional study - Ryadul Alam; Sadia Akter; Tanaa Mohammad; Rowshanara Rini; Mst Mariyam; Afrana Akter Priti; Aishwaria Mitra Ayshee; Md Shahriar Hossen Sayem; Afsana Mohammad Mimi; Ayesha Ahmed; Lakshmi Rani Kundu; Md. Habibullah Talukder; et al. (PLoS ONE, 2026)
Breast cancer is a leading cause of cancer-related deaths worldwide, with most cases in Bangladesh diagnosed at advanced stages due to limited awareness and late detection. While breast self-examination (BSE) is a simple, cost-free method for early detection, its practice among adolescents remains poorly understood. This study aims to explore breast cancer knowledge, BSE practices, and barriers among adolescent girls in a semi-urban area, addressing a critical gap in early prevention efforts. A cross-sectional study was carried out with 384 adolescent girls from four renowned schools in a semi-urban area of Dhaka, Bangladesh. Participants were sampled at school from January to April 2025. Proportionate stratified random sampling was conducted to determine the study sample from each school. A validated semi-structured self-reported questionnaire was employed to collect data from participants during the survey period. Among the participants, only 45.3% had heard of BSE and just 4.6% reported ever practicing it. Overall, breast cancer knowledge was low, with a mean score of 9.49 out of 31 (30.6%). Regression analyses indicated that higher breast cancer knowledge scores were significantly associated with having a science academic background (β = 1.82, p < 0.01), higher family income (β = 1.14, p < 0.05), and prior BSE practice (β = 2.36, p < 0.001). A strong positive correlation was observed between overall knowledge and BSE practice (r = 0.54, p = 0.001). Students from the science section were significantly more likely to practice BSE than those from the humanities section (OR = 9.47, 95% CI: 1.21–73.89, p = 0.032). Participants who received BSE information from health workers were approximately nine times more likely to practice BSE than those who did not (OR = 9.62, 95% CI: 2.30–40.20, p = 0.002). The study demonstrates critically low levels of breast cancer knowledge and BSE practice among adolescent girls, with knowledge strongly influencing practice. These findings underscore the need for culturally appropriate, school-based educational interventions to improve awareness, promote early detection behaviors, and potentially reduce future breast cancer morbidity and mortality in Bangladesh.